Spatial Genetic Structure and Demographic History of the Dominant Forest Oak Quercus fabri Hance in Subtropical China - Chen, Xiao-Dan; Yang, Jia; Guo, Yu-Fan; Zhao, Yue-Mei; Zhou, Tao; Zhang, Xiao; Ju, Miao-Miao; Li, Zhong-Hu; Zhao, Gui-Fang (Frontiers in Plant Science, 2021)
Oak trees (Quercus L.) are important models for estimating abiotic impacts on the population structure and demography of long lifespan tree species. In this study, we generated genetic data for 17 nuclear microsatellite loci in 29 natural populations of Quercus fabri to estimate the population genetic structure. We also integrated approximate Bayesian computation (ABC) and ecological niche analysis to infer the population differentiation processes and demographic history of this oak species. The genetic analyses indicated two genetic clusters across the 29 populations collected, where most approximately corresponded to the intraspecific differentiation among populations from western and eastern China, whereas admixed populations were mainly found in central mountains of China. The best model obtained from hierarchical ABC simulations suggested that the initial intraspecific divergence of Q. fabri potentially occurred during the late Pliocene (ca. 3.99 Ma) to form the two genetic clusters, and the admixed population group might have been generated by genetic admixture of the two differentiated groups at ca. 53.76 ka. Ecological analyses demonstrated clear differentiation among the Q. fabri population structures, and association estimations also indicated significant correlations between geography and climate with the genetic variation in this oak species. Our results suggest abiotic influences, including past climatic changes and ecological factors, might have affected the genetic differentiation and demographic history of Q. fabri in subtropical China.